Endoscopic tympanoplasty with inlay cartilage graft in an university hospital - Pontes-Madruga,Thaís de Carvalho (2021)
Abstract Introduction Tympanoplasty is the surgical procedure aimed at the reconstruction of the tympanic membrane and restoration of the sound conducting mechanism. It can be performed with several types of access and grafts and is considered successful when it achieves complete closure of the tympanic perforation and sound conduction improvement. Objective To describe the prevalence of successful closure of tympanic perforations and auditory results of endoscopic tympanoplasty with an inlay tragus cartilage graft. Methods Retrospective study developed at a tertiary referral hospital. Patients with central tympanic perforations and intact ossicular chains operated with endoscopic tympanoplasty with inlay tragus cartilage graft were included. The neo-tympanum integrity index was evaluated, and the preoperative and postoperative auditory parameters were compared using the paired Student's t-test. Results We identified 83 endoscopic tympanoplasties with inlay cartilage, of which 63 (76 %) had an intact neo-tympanum and 20 (24 %) had residual perforations. The preoperative air-bone gap was, on average, 18 ± 8.9 dBHL, and the postoperative 11 ± 10 dBHL (p = 0.0005), showing reduction in 71 % and complete recovery in 27 %. The mean preoperative speech recognition threshold was 35 ± 13.5 and the postoperative SRT was 27 ± 14.4 (p = 0.0002). The preoperative tritonal mean was 34 ± 14.3 and the postoperative was 24 ± 15 (p = 0.0002). Conclusion In this series, endoscopic tympanoplasties with inlay tragus cartilage graft showed a 76 % prevalence of complete closure of the tympanic perforation, with significant improvement in the auditory parameters.